Letter (copy) : Voluntary industrial aid - Tewson, Vincent
036-0035-001 GP/LJL. HVT/EK/802. Secretary's. 30th April, 1937. Mr. G. Pyke , Voluntary Industrial Aid for Spain, 32, Great Ormond Street, LONDON, W.C.1. Dear Mr. Pyke, VOLUNTARY INDUSTRIAL AID. Referring to your letter of the 18th April, it was felt that the only really satisfactory course was for us to communicate with our affiliated Unions concerned. We have sent a letter to them in sympathetic terms and as soon as we receive all the replies we will again communicate with you. There may appear to be some delay in this matter, but you will appreciate it is far preferable for us to proceed with a full knowledge of the official attitude of our Unions than to meet difficulties at a later stage. Yours sincerely, Assistant Secretary. 292/946/36/35